Influence of Online Platforms on Tourist Behaviours : A Case Study of Paara Safari Lodge - Priscilla Kaakyo (Uganda Christian University, 2023)
This study explores the impact of online platforms on tourist behavior in Uganda's tourism sector, highlighting the challenges faced by rural areas and the digital divide. Factors like online reviews, satisfaction levels, and information access can significantly shape tourist behavior. International tourists dedicate more time to online platforms, expressing high satisfaction levels. Booking preferences vary, with weekly usage hours ranging from 3 to 10. Bridging the digital gap is crucial for sustainable growth in Uganda's tourism sector. Results revealed that International tourists spend more time on online platforms for travel-related activities than domestic tourists, indicating a significant disparity in online behavior. These platforms provide essential travel details, cultural insights, and booking options, facilitating global mobility and contributing to the growth of the tourism industry. High satisfaction ratings indicate the effectiveness of online platforms in meeting travelers' needs and influencing booking decisions. The data also shows a substantial increase in bookings made through online channels, reflecting the industry's adaptability to changing consumer preferences. Paara Safari Lodge's diverse activities cater to a diverse range of tourists.
This is a dissertation.